2023
DOI: 10.1097/mao.0000000000003794
|View full text |Cite
|
Sign up to set email alerts
|

Video Head Impulse Test Demonstrates a Residual Function after Plugging of Dehiscent Superior Semicircular Canal

Abstract: ObjectivePlugging a symptomatic dehiscent superior semicircular canal (SSCC) often leads to a nonfunctional postoperative canal. However, in some instances, a residual function has been described. This study attempts to describe what factors may lead to such residual function.Study designRetrospective study.SettingTertiary referral center.PatientsThirty-five patients with confirmed SSCC dehiscence.InterventionVideo head impulse test was conducted pre- and postoperatively to assess any difference in the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Accordingly, both patients reported an improvement in both auditory and vestibular symptoms after surgery. The lady who underwent canal plugging developed a transient global vestibular hypofunction overlapping the postoperative findings in patients after SSC occlusion in SSCD [48,50,51]. On the other hand, the man who underwent RW reinforcement developed symptoms due to a contralateral HSCD with the FN after surgery, similar to what has been described in patients with multiple third window disorders, highlighting the importance of an extensive preoperative clinical, instrumental and radiological assessment [13].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Accordingly, both patients reported an improvement in both auditory and vestibular symptoms after surgery. The lady who underwent canal plugging developed a transient global vestibular hypofunction overlapping the postoperative findings in patients after SSC occlusion in SSCD [48,50,51]. On the other hand, the man who underwent RW reinforcement developed symptoms due to a contralateral HSCD with the FN after surgery, similar to what has been described in patients with multiple third window disorders, highlighting the importance of an extensive preoperative clinical, instrumental and radiological assessment [13].…”
Section: Discussionsupporting
confidence: 62%
“…Recently, alternative mechanisms have been offered to explain how some SSCD patients with SSC hypofunction on vHIT still exhibit symptoms and signs consistent with a TMWM. In fact, a TMWM is expected to fade after a spontaneous canal occlusion, similarly to what it is expected from a surgical canal plugging [48][49][50][51]. An incomplete canal occlusion or a membranous canal indentation at the dehiscence leading to an endolymphatic flow dissipation during impulsive tests have been recently hypothesized [47,49].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Through MCFA plugging, there may be a lower risk of sensorineural hearing loss to the SSC and/or vestibular function impairment in the other canals ( 3 , 8 ). In addition, a recently published study by Renteria et al demonstrated residual SSC function 3 months postoperatively in 55.3% of patients operated on for SSC dehiscence through the MCFA ( 9 ). On the other hand, the TMA avoids craniotomy and temporal lobe retraction and remains the preferable approach for cases of medial and purely posterior dehiscence ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found pathological vHIT function in four of six superior semicircular canals preoperatively, of which some normalized after surgery. The previously proposed auto-plugging hypothesis suggests that dural herniation and compression of the membranous labyrinth imped normal endolymphatic flow and normal VOR response (5,16,36–38). However, the dural compression must create insufficient occlusion as the four patients with abnormal VOR response were both symptomatic and showed objective measures of a third window by VEMP and audiometric testing.…”
Section: Discussionmentioning
confidence: 99%